2016
DOI: 10.1093/mnras/stv2859
|View full text |Cite
|
Sign up to set email alerts
|

A young star-forming galaxy atz= 3.5 with an extended Lyman α halo seen with MUSE

Abstract: A young star-forming galaxy at z = 3.5 with an extended Lyman α halo seen with MUSE ABSTRACTSpatially resolved studies of high redshift galaxies, an essential insight into galaxy formation processes, have been mostly limited to stacking or unusually bright objects. We present here the study of a typical (L * , M = 6 ×10 9 M ) young lensed galaxy at z = 3.5, observed with MUSE, for which we obtain 2D resolved spatial information of Ly α and, for the first time, of C iii] emission. The exceptional signal-to-noi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 75 publications
6
105
1
Order By: Relevance
“…(1) Baldry et al (2014); (2) Bacon et al (2015); (3) this work; (4) Patrício et al (2016). See also http://classic.sdss.org/dr5/algorithms/spectemplates/ for templates No.…”
Section: Appendix A: Muse Udf Redshift Catalogsmentioning
confidence: 99%
“…(1) Baldry et al (2014); (2) Bacon et al (2015); (3) this work; (4) Patrício et al (2016). See also http://classic.sdss.org/dr5/algorithms/spectemplates/ for templates No.…”
Section: Appendix A: Muse Udf Redshift Catalogsmentioning
confidence: 99%
“…Rix et al (2004), and later on Sommariva et al (2012) showed that several blends of stellar UV photospheric absorption lines can be used to trace the metallicity of young stars, by measuring equivalent widths of these blends in specific wavelength windows. These metallicity indicators have been successfully applied in several works (e.g., Quider et al 2009Quider et al , 2010Patrício et al 2016), using high S/N spectra due to the faintness of these absorption lines. They are defined as the F1370, F1425, F1460, F1501, and F1978 indices, and their wavelength windows are shown in Figure 2 (except for the latter one which is not covered by our data).…”
Section: Kinematics Of the Ismmentioning
confidence: 99%
“…In compiling the data for Figure 9, we include observations at redshifts z<4 from Jones et al (2013) (not shown in Table 1), Reddy et al (2016), and Patrício et al (2016). Across this increased redshift range, the figure shows that we cannot yet detect any significant time dependence.…”
Section: Redshift Evolution and Reonizationmentioning
confidence: 99%
“…The color scheme follows that in Figure 8. The black error bar and the black data point show f cov,obs derived from lowionization absorption profiles, in a stacked spectrum of z∼3 galaxies from Reddy et al (2016) and in a spectrum of a lensed z = 3.5 galaxy from Patrício et al (2016), respectively.…”
Section: Redshift Evolution and Reonizationmentioning
confidence: 99%